2010
DOI: 10.1074/jbc.m110.137257
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized Cholesteryl Esters and Phospholipids in Zebrafish Larvae Fed a High Cholesterol Diet

Abstract: A novel hypercholesterolemic zebrafish model has been developed to study early events of atherogenesis. This model utilizes optically transparent zebrafish larvae, fed a high cholesterol diet (HCD), to monitor processes of vascular inflammation in live animals. Because lipoprotein oxidation is an important factor in the development of atherosclerosis, in this study, we characterized the oxidized lipid milieu in HCD-fed zebrafish larvae. Using liquid chromatography-mass spectrometry, we show that feeding an HCD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 25 publications
(47 reference statements)
5
88
0
Order By: Relevance
“…Previous reports have demonstrated that zebrafish larvae become hypercholesteremic upon treatment with HCD, exhibiting increased total cholesterol and vascular plaques after 10 days of treatment ( 35,42,43 ). It is unknown, however, if hypercholesteremia in zebrafi sh can result from perturbation of gene expression.…”
Section: Mo Injection Disrupts Ldlr Expression Through Early Developmentmentioning
confidence: 99%
“…Previous reports have demonstrated that zebrafish larvae become hypercholesteremic upon treatment with HCD, exhibiting increased total cholesterol and vascular plaques after 10 days of treatment ( 35,42,43 ). It is unknown, however, if hypercholesteremia in zebrafi sh can result from perturbation of gene expression.…”
Section: Mo Injection Disrupts Ldlr Expression Through Early Developmentmentioning
confidence: 99%
“…Cholesterol-fed zebra fish represent a novel animal model in which to study the early events involved in vascular lipid accumulation and lipoprotein oxidation [114,115]. Feeding zebra fish a high-cholesterol diet results in hypercholesterolaemia, vascular lipid accumulation, myeloid cell recruitment, and other pathological processes characteristic of early atherogenesis in mammals [113].…”
Section: Zebra Fishmentioning
confidence: 99%
“…M2 cells can inhibit the inflammatory response and facilitate the recovery of tissue injuries via the release of IL-10, arginase, and the scavenger receptor (Spivia et al, 2014). It is interesting to note that the major component of atherosclerotic plaques, oxygenated cholesterol, primarily facilitates the differentiation of M1 cells through activation of the MAP signaling pathway (Fang et al, 2010). All of these studies support a critical role of M1/M2 cell differentiation in the pathogenesis and progression of atherosclerosis.…”
Section: Discussionmentioning
confidence: 80%